The application of DTI to investigate abnormalities in schizophrenia and alzheimer disease (2015)
The objective of this study was to evaluate in individuals applications at clinical high risk of mental disorder with Diffusion Tensor Imaging (DTI-MRI). This provides an important opportunity for pathological mechanisms of Schizophrenia Disease (SD) and Alzheimer Disease (AD), related to mental disorder. All disease is associated with abnormal activity distributed spatially in neural systems with mediate the motor and cognitive manifestations of this disorder in combination with processing and visualization techniques for Diffusion Tensor Magnetic Resonance Imaging (DTI-MRI). It is possible that metabolic MRI studies have demonstrated that this illness is characterized by a set of reproducible functional brain networks that correlate with these clinical features. The time at which these abnormalities appear is unknown, as is their relationship to concurrent clinical and indices of disease progression. We therefore need to set vivo biomarkers that can distinguish the differing pathologies and their contribution to the clinical features of the conditions. Diffusion tensor imaging (DTI) utilizes the anisotropic nature of diffusion in neuronal white matter tracts. With neuronal degeneration, the mean diffusivity (MD) increases with the loss of structural barriers that restrict normal diffusion, and diffusion becomes less directionally oriented, which is associated with a reduction in fractional anisotropy (FA). Areas of reduced FA in subjects with lateral ventricle were found primarily in occipital parietal area with white matter tracts; in AD, it was also associated with reduced FA in the points the left thalamus. © 2015, Scientific Publishers of India. All rights reserved.